Correction: High thermoelectric performance in complex phosphides enabled by stereochemically active lone pair electrons. Issue 3 (19th December 2018) - Shen, Xingchen; Xia, Yi; Wang, Guiwen; Zhou, Fei; Ozolins, Vidvuds; Lu, Xu; Wang, Guoyu; Zhou, Xiaoyuan
Abstract : Correction for 'High thermoelectric performance in complex phosphides enabled by stereochemically active lone pair electrons' by Xingchen Shen et al., J. Mater. Chem. A, 2018, 6, 24877–24884.